الحقوق والحريات في منهج الفلسفة للصف الثاني الثانوي الفرع الأدبي دراسة تحليلية تقويمية مقارنة في الكتابين القديم والجديد - سلوم, طاهر; سيف الدين, حسين (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
يهدف البحث للكشف عن مفاهيم الحقوق والحريات في مضمون كتاب الفلسفة القديم، والكتاب الجديد للصف الثاني الثانوي الفرع الأدبي في الجمهورية العربية السورية، وتقديم وصف كمي للمهتمين بتطوير المناهج ، والكشف عن التطور الحاصل في مضمون الكتاب الجديد عنه في الكتاب القديم، تكوّن معيار التحليل وفق اقتراحات لجنة التحكيم من ثلاثة عشر مفهوماً لفئة الحقوق، ومثلها لفئة الحريات، وأجرى الباحث تجربتي تحليل، واستعان بمحللين آخرين للتأكد من صدق وثبات المعيار، ثم وضع لبحثه عدداً من الفرضيات، وقام باختبارها وتوصّل إلى النتائج الآتية: 1ـ لا يوجد فرق في عدد التكرارات المسجلة من الكتابين. 2ـ يوجد فرق لصالح الكتاب الجديد في عدد تكرارات فئة الحقوق. 3ـ يوجد فرق لصالح الكتاب القديم في عدد تكرارات فئة الحريات. 4ـ يوجد في التكرارات المسجلة من مضمون الكتابين لصالح مفهوم الحقوق الفردية. 5ـ يوجد في التكرارات المسجلة من مضمون الكتابين لصالح مفهوم الحرية المجرد. وأما نتائج الإجابة على أسئلة البحث: 1ـ يوجد فرق في شكل العرض ويعود لصالح الكتاب الجديد. 2ـ يوجد فرق في اتجاه العرض وهو لصالح الكتاب الجديد. 3ـ يوجد فرق في أسلوب وطريقة تنظيم المضمون وتقديمه، والفرص لصالح الكتاب الجديد. This study aims at discovering the rights and the librates concepts in the new and the old books of philosophy in the second secondary class – literary section. The instrument of measuring these concepts in this study is a list consists of (26) items distributed in two domains (the rights and the liberties). Each one of these domains contains (13) concepts. According to the hypothesis the results show that: 1- There is a statistically significant difference in the number of frequencies registered in the two books. 2- There is a statistically significant difference in the number of frequencies registered in (the liberty domain) in favor of the old book. 3- There is a statistical significant difference in the number of frequencies registered in (the rights domain) in favor of the new book. 4- There is a statistical significant difference in the number of frequencies registered in the sub- concepts (in the rights domain) in favor of the two books. 5- There is a statistical significant difference in the number of frequencies registered in the sub- concepts (in the liberty domain) in favor of the ambiguous liberate concept in favor of the new book According to the questions the results show that: 1- There is a difference in the manner of displaying the content in favor of the new book. 2- There is a difference in the shape of displaying the content in favor of the new book. 3- There is a difference in organizing the content in favor of the new book.